Strengthening the Character Education of Alpha Generation through a Mosque-Based Maghrib Mengaji Program: A Qualitative Study - Mahathir Akbar; Didi Mustahdi; Dudung Abdul Rohman; Sifa Syahidah (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
The rapid development of digital technology has brought significant changes to the behavior and character formation of Generation Alpha, creating challenges for Islamic character education in both formal and non-formal educational settings. As a community-based Islamic educational institution, the mosque has a strategic role in strengthening children's character through religious habituation programs. This study aims to analyze the implementation of the Maghrib Mengaji Program, identify the character values developed, examine the role of the mosque in strengthening character education, and explore the supporting and inhibiting factors in implementing the program at Al-Hidayah Mosque, Gandawesi Village, Ligung District, Majalengka Regency. This research employed a qualitative approach using a case study design. Data were collected through observations, semi-structured interviews, and documentation involving mosque administrators, Qur'anic teachers (ustadz), parents, and program participants. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. The findings reveal that the Maghrib Mengaji Program is implemented systematically through congregational Maghrib prayer, Qur'anic learning, tahsin, memorization of short surahs, Islamic moral instruction, and continuous religious habituation. The program successfully strengthens religious character, discipline, responsibility, honesty, independence, politeness, and social awareness among Generation Alpha. Its success is supported by collaboration among mosque administrators, teachers, parents, and the local community, while challenges include excessive digital device use, limited teaching personnel, and inconsistent participant attendance. This study concludes that the Maghrib Mengaji Program represents an effective mosque-based model of non-formal Islamic education for strengthening the character of Generation Alpha through the integration of Qur'anic learning, exemplary practices, religious habituation, and community participation.